Emergency medical services: Safety awareness between teaching and public hospital - Saad, Shahzuwaty; Tuan Kamauzaman, Tuan Hairulnizam; Ibrahim, Mohd Ismail; Saad, Shatina (2014)
Increased in demand from the public for a better Emergency Medical Services (EMS) have alert the Malaysia Ministry of Health to increase the quality of this services as it act as a front line.Emergency medical provider deals with any patient from their homes and street to the hospital door in pre-hospital care, from the non-critical to the most critical cases in the department, and for society from all strata of life.In order to give the best service and as a front line medical provider, acquiring a very good safety culture in the workplace is important so that they can serve and give the best services to the patient.The purpose of this article is to identify the safety awareness in workplace between teaching and public hospital at emergency medical services provider.This paper also offers a review of work culture in EMS as a front line of the medical services.Results of the survey later will be explained by the statistic provided.This will serve as a guideline for emergency medical provider on the knowledge about the importance of safety awareness at the workplace.